Rhythms of Religious Ritual The Yearly Cycles of Jews, Christians, and Muslims - Black, Kathleen (Claremont Studies in Interreligious Dialogue, 2018)
This volume explores the religious calendars and observances of Judaism, Christianity and Islam.